Kesejahteraan Siswa Di Sekolah Studi Komparasi Pada Sekolah Yang Mengimplementasikan Program Pendidikan Sekolah Adiwiyata Dan Belum Mengimplementasikan Program Pendidikan Sekolah Adiwiyata Di SMP - Nur Rizkasari, Oktiana, Usmi Karyani, S.Psi., M.Si (2017)
Students feel weelbeing when they feel comfortable, safe, happy and healthy in their school. Associated with the welfare of students who cause students weelbeing is the physical environment of the school environment, school social relations and fulfillment in school. The problem that often happens is the school is not paying attention to the physical condition of the school environment that makes students feel hot in the classroom, students are not comfortable in class, and students do not get good nutrition in school. One effort to create a weelbeing school is through adiwiyata school by making the school physical environment clean, shady and cool. The purpose of this study is to compare the welfare of students in schools implementing adiwiyata school programs and those who have not implemented school adiwiyata programs and to describe differences in the weelbeing of students in schools that implement adiwiyata school programs and those who have not implemented adiwiyata school programs. The method of this research is mixed methode is a combination of quantitative and qualitative data using sequential explanatory. Subjects for the quantitative data of men amounted to 167 students and women amounted to 207 students, for the subject of qualitative data in this study amounted to 2 people. Methods of data collection using questionnaires and semi-structured interviews. The results of this study is that there are differences in the level of weelbeing of students in schools that have implemented adiwiyata school education programs and who have not implemented adiwiyata school education program. The difference lies in the development of school policies, curriculum structures, the development of activities, and the provision of infrastructure. So that this adiwiyata program can be continued and reproduced schools that implement adiwiyata school education program.